2000
DOI: 10.1037/0735-7044.114.4.687
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of place and cue learning by telencephalic ablation in goldfish.

Abstract: This study examined the spatial strategies used by goldfish (Carassius auratus) to find a goal in a 4-arm maze and the involvement of the telencephalon in this spatial learning. Intact and telencephalon-ablated goldfish were trained to find food in an arm placed in a constant room location and signaled by a local visual cue (mixed place-cue procedure). Both groups learned the task, but they used different learning strategies. Telencephalon-ablated goldfish learned the task more quickly and made fewer errors to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 117 publications
(202 reference statements)
4
66
0
Order By: Relevance
“…3B). Interestingly, the involvement of the lateral pallium of goldfish in spatial cognition seems to be selective to place learning, as damage to this area does not impair cue learning or other egocentric strategies [Salas et al, 1996a, b;Ló pez et al, 2000a;Rodríguez et al, 2002b]. In summary, these results demonstrate a striking functional similarity between the hippocampal pallium of amniotes and the lateral pallium of the telencephalon of the teleost fish.…”
Section: Spatial Memory and Telencephalic Pallium In Actinopterygian mentioning
confidence: 58%
See 1 more Smart Citation
“…3B). Interestingly, the involvement of the lateral pallium of goldfish in spatial cognition seems to be selective to place learning, as damage to this area does not impair cue learning or other egocentric strategies [Salas et al, 1996a, b;Ló pez et al, 2000a;Rodríguez et al, 2002b]. In summary, these results demonstrate a striking functional similarity between the hippocampal pallium of amniotes and the lateral pallium of the telencephalon of the teleost fish.…”
Section: Spatial Memory and Telencephalic Pallium In Actinopterygian mentioning
confidence: 58%
“…3C-D). In fact, the place memory deficit observed after lateral pallium lesions in goldfish is as severe as that produced by the complete ablation of both telencephalic hemispheres [Salas et al, 1996a, b;Ló pez et al, 2000a;Rodríguez et al, 2002a, b]. In contrast, medial or dorsal pallium lesions do not produce any observable impairment in place learning [Rodrí-guez et al, 2002b] (fig.…”
Section: Spatial Memory and Telencephalic Pallium In Actinopterygian mentioning
confidence: 99%
“…Studies by Van Staaden et al [1995] and Huber et al [1997] also found larger telencephalons in cichlid species living in more spatially complex habitats created by shallow rock and vegetation compared to those species living in mid-water. A number of studies have provided evidence for the telencephalon's involvement in various complicated behaviours such as spatial learning [Salas et al, 1996a, b;López et al, 2000], avoidance responses [Portavella et al, 2003[Portavella et al, , 2004, territoriality, shoaling [Shinozuka and Watanabe, 2004;Martín et al, 2011] and reproductive behaviours such as mating strategy, courtship, nest building and parental care [Overmeir and Gross, 1974;Koyama et al, 1984;Pollen et al, 2007;Broglio et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…These early findings confirm the role of the telencephalon in spatial behavior of fish, but they also relate to the general debate about the existence of successive reversal learning in fish. Overmier and Hollis (1990) reported that fish without brain lesions "[did not] improve when they were repeatedly required to reverse successfully the previous trained response" (p. 217), and the telencephalon ablated fish were different only in the fact that, compared to the "normal" fish which did not reduce errors across reversals, they actually showed lower performance across successive reversals, Interestingly, the subsequent findings of López, Bingman, Rodríguez, Gómez, and Salas (2000) seem to contradict the conclusions of Overmier and Hollis (1990). Lopez et al found that goldfish with bilateral telencephalic ablation, sham operated or intact, were successfully trained in a spatial constancy task or in a directly cued task.…”
Section: Spatial Learningmentioning
confidence: 90%